Online writing research in the upper-division composition classroom: constructions of social engagement and critical dialogue - Welker, Alyson, author; Jennings, Louise, advisor; Gloeckner, Gene, committee member; Lynham, Sue, committee member; Doe, Sue, committee member (Colorado State University. Libraries, 2020)
This dissertation is comprised of three related articles examining social engagement and critical dialogue practices in the upper-division online writing classroom. The three manuscripts are presented with bookend chapters to introduce and discuss the larger research project. The over-arching questions this research asks are: How are teaching and learning supported and constrained in online writing instructional environments? How can constructions of social engagement in the online Writing Arguments classroom support critical learning and critical dialogue? The three articles examine the teaching of writing in an upper-division online writing course, Writing Arguments, which is a rhetorical theory course in composition. This compilation of continually evolving research captures the dual importance of enhancing online education as well as the need to construct social engagement in the online classroom. Additionally, as the Writing Arguments course lends itself naturally to areas of opposition and difference, the final two studies focus specifically on critical dialogue and learning in the online classroom.
Keywords: critical pedagogy online; online education; online writing instruction; online composition research; critical dialogue in online education; online education research